Exploring the adoption of green accounting practices in Vietnamese small and medium enterprises - Hùng Phạm Huy (West Science Accounting and Finance, 2024)
This research addresses the gap in understanding the adoption of green accounting among small and medium enterprises (SMEs) in Vietnam, particularly in the context of developing economies where such practices are underexplored. The purpose of the research was to investigate the awareness, motivations, barriers, and current practices of SMEs regarding green accounting, aiming to understand how these businesses can better integrate environmental costs into their financial operations. A qualitative approach was used, involving semi-structured interviews with 6 SME owners, 5 CFOs and 4 accountants from 10 SMEs across a range of sectors (manufacturing, agriculture and tourism), the interview data was analysed using thematic analysis to identify key themes relating to green accounting awareness, adoption drivers and barriers. The results revealed that while awareness of green accounting is growing, it remains limited, with most SMEs driven by external pressures such as regulatory compliance and customer demand. However, barriers such as financial constraints, operational challenges, and knowledge gaps hinder widespread adoption. The significance of these findings lies in their implications for policymakers and industry leaders, suggesting that targeted incentives, training programs, and stronger regulatory frameworks can help overcome these barriers. Enhancing support for SMEs in adopting green accounting can lead to more sustainable business practices, improved competitiveness, and better environmental outcomes.